K uplývající přítomnosti: Jedinečnost a opakování v sociálním jednání - Jakub Mlynář (Acta Universitatis Carolinae: Philosophica et Historica)
Temporality is a fundamental dimension of human existence and social reality. In this article, I explore some implications for sociology arising from the tension between uniqueness and repetition. I propose that sociology should focus on what I term the “transient present”, which I conceive as the locus of the production of social structures. From this shifting center, the past and future emerge continuously in each moment as locally relevant, interactively actualized cultural objects. I illustrate the themes of this investigation using a publicly available video recording of a dispute between two London cyclists. I conclude by discussing the implications of emphasizing the transient present for sociological thinking, such as challenging the axiom of the human actor or the assumption that society consists of multiple individuals. I highlight that the emergence of the present is not primarily a theoretical problem but a methodological principle and analytical orientation for empirical inquiry. This approach enables describing and explicating how social structures, facts and actors are practically constituted, maintained, and sometimes abandoned in the everyday objectivity of lived time.